Strong Convergence of a Modified Extragradient Method to the Minimum-Norm Solution of Variational Inequalities - Yonghong Yao; Muhammad Aslam Noor; Yeong-Cheng Liou (Abstract and Applied Analysis)
We suggest and analyze a modified extragradient method for solving variational inequalities, which is convergent strongly to the minimum-norm solution of some variational inequality in an infinite-dimensional Hilbert space.